Hybrid Green Technology Adoption in Indonesian MSMEs: A Conceptual Readiness Model - Albert William Wibisono (Journal of Research on Business and Tourism, 2025)
As Indonesia advances its commitments to digital transformation and environmental sustainability, Micro, Small, and Medium Enterprises (MSMEs) face structural constraints that limit the adoption of high-cost green and digital technologies. Existing frameworks often treat digitalization and sustainability as separate and resource-intensive processes, creating barriers for MSMEs operating with limited capital and capabilities. This study develops a conceptual Hybrid Green Technology Readiness Model that integrates the Twin Transition framework with principles of frugal innovation. Using a structured synthesis of recent literature on MSME digital maturity, sustainability readiness, and low-cost technology adoption, this study proposes a readiness matrix based on two dimensions: digital maturity and ecological awareness. The model demonstrates that basic digital tools, such as cloud-based services, digital payments, route optimization, and simple inventory systems, can simultaneously enhance operational efficiency and reduce environmental impact. By reframing sustainability as an efficiency-driven and value-creating process rather than a compliance burden, the proposed framework offers a practical pathway for MSMEs in developing economies. This study contributes to sustainability and entrepreneurship literature by providing a context-sensitive and accessible model to support inclusive green and digital transformation in Indonesian MSMEs.